A LEGAL PROTECTION EFFORTS CREDITORS WITHOUT THE CREDITOR'S PERMISSION THE UNREGISTERED FIDUCIARY SECURITY OBJECT IS TRANSFERRED BY THE DEBTOR - Khomaini Khomaini; Winta Hayati (Sean Institute, 2022)
As a state of law, the laws regulated in Indonesia will always develop along with the times to meet the needs of Indonesian society. The enactment of the Fiduciary Guarantee Law (UUJF) Number 42 of 1999 is sufficient to fulfill the needs of the community in the practice of consumer financing with the Fiduciary Guarantee system, in which it regulates how to carry out Fiduciary Guarantee and the form of legal protection for both Creditors and Debtors. Article 36 of UUJF states that a Fiduciary who transfers, mortgages, or leases an object of Fiduciary Guarantee as referred to in Article 23 Sub (2) of UUJF without the prior written consent of the Fiduciary Recipient shall be punished with imprisonment for a maximum of 2 (two) years and a maximum fine of Rp 50,000,000,- (fifty million rupiah). The need to provide legal certainty in order to form legal protection from a rule of law. So by registering the Fiduciary Guarantee deed at the Registration Office of the Ministry of Law and Human Rights of the Republic of Indonesia, as well as the inclusion of a clause containing the prohibition of transferring the object of the Fiduciary Guarantee in the agreement deed is the right step in protecting the parties. Therefore, any transfer of the Fiduciary Guarantee object must be based on the provisions in the UUJF, so that there is legal protection for the Creditor in the event that the Debtor transfers the Fiduciary Guarantee object that has not been registered without the Creditor's permission.